The Effect of Bid Ask Spread, Market Value and Risk Of Return on the Holding Period of LQ45 Stocks on the Indonesia Stock Exchange - Tio Winda Sitompul (Institute of Computer Science (IOCS), 2021)
The purpose of this study is to investigate and to analyze the effect of the bid ask spread, market value, and the risk of return to the holding period LQ45 in Indonesia Stock Exchange Period February 2008 to January 2012. Secondary data collection is done by recording the closing price, the number of shares outstanding, trading volume, bid price, ask price and download financial statements published by the Indonesia Stock Exchange and quoted from a written source that is used as a theoretical basis. The analytical method used was multiple linear regression analysis. This research samples using 76 companies listed in the index always LQ45. The results showed that the bid ask spread, market value, and the risk of return simultaneously effect holding period for shares with a significance level (α= 5%). Partially, the bid ask spread and market value and no significant positive effect on the holding period return while the risk of a negative and significant effect on the holding period LQ45 in Indonesia Stock Exchange Period February 2008 to January 2012.